Pengaruh Model Pembelajaran Inkuiri terhadap Kemampuan Pemecahan Masalah pada Materi Usaha dan Energi - Siti Zukhairia; Sabani (Mataram University, 2026)
This study aims to determine the improvement in students' problem-solving skills and the effect of the inquiry learning model on these skills regarding the topic of work and energy in Grade XI at a public high school in Medan. Twenty-first century education requires student-centered learning to develop critical thinking and problem-solving skills. However, students' problem-solving abilities remain relatively low, as reflected in TIMSS and PISA results, while physics instruction is still predominantly teacher-centered and emphasizes memorization rather than inquiry and contextual problem solving. The study was motivated by students' low problem-solving abilities in physics lessons—which remain dominated by conventional methods—resulting in a lack of active student engagement in understanding concepts and solving problems systematically. A quasi-experimental method with a two-group pretest-posttest design was employed. The study population consisted of all Grade XI Science students at a public high school in Medan during the 2025/2026 academic year. The sample comprised two classes selected via cluster random sampling: an experimental class receiving inquiry-based instruction and a control class receiving conventional instruction. The research instrument was a problem-solving skills test based on Heller’s indicators: focusing on the problem, describing the physics, planning the solution, executing the plan, and evaluating the solution. Data analysis involved validity and reliability testing, prerequisite testing, and N-gain analysis. The results indicate that the inquiry learning model leads to greater improvement in problem-solving skills compared to conventional instruction. Implementing this model encourages students to be more active in the learning process and think critically, while also enabling them to connect physics concepts with problem-solving in real-life contexts.